Injury characteristics in the German professional male soccer leagues after a shortened winter break - aus der Fünten, K.; Faude, O.; Lensch, J.; Meyer, T. (Journal of Athletic Training, 2015)
Context: The winter break in the top 2 German professional soccer leagues was shortened from 6.5 to 3.5 weeks in the 2009-2010 season.